2020
DOI: 10.1111/cobi.13605
|View full text |Cite
|
Sign up to set email alerts
|

Threats posed to conservation by media misinformation

Abstract: Media misinformation is an increasing concern in conservation; for example, climate change denial is particularly pervasive (Wong-Parodi & Feygina 2020). Here, we highlight simplistic and inaccurate coverage of trophy hunting (TH) in mainstream newspapers (print and online). This is particularly timely because the United Kingdom and the United States are considering laws to restrict or ban trophy imports and exports (DEFRA 2019; U.S. Congress 2019). The dominant media narrative is beguilingly simple: well-love… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…In most cases, 'smart regulation' will be needed, whereby a combination of instruments are used to create an appropriate policy mix, which can flexibly, efficiently and equitably incentivize multiple stakeholders and institutions (Young and Gunningham, 1997;Gunningham and Sinclair, 2017). Wildlife trade is also a highly emotive topic, and policy decisions can be influenced by strong public opinions, which aren't necessarily rational or data-driven (Hart et al, 2020). More transparent approaches to decisionmaking are needed to address wildlife trade in the face of public health crises and beyond, wherein decision criteria and costs and benefits are clearly outlined and publicly available.…”
Section: Implementing a Risk-based Approach To Wildlife Trade Policy:mentioning
confidence: 99%
“…In most cases, 'smart regulation' will be needed, whereby a combination of instruments are used to create an appropriate policy mix, which can flexibly, efficiently and equitably incentivize multiple stakeholders and institutions (Young and Gunningham, 1997;Gunningham and Sinclair, 2017). Wildlife trade is also a highly emotive topic, and policy decisions can be influenced by strong public opinions, which aren't necessarily rational or data-driven (Hart et al, 2020). More transparent approaches to decisionmaking are needed to address wildlife trade in the face of public health crises and beyond, wherein decision criteria and costs and benefits are clearly outlined and publicly available.…”
Section: Implementing a Risk-based Approach To Wildlife Trade Policy:mentioning
confidence: 99%
“…Many seizure events in a given country may not be reported by the international media but rather by local newspapers only (Nijman, 2015;Paudel et al, 2020). Besides this, due to publication pressure, media outlets may lack the time or resources to conduct first-hand investigation and thus may repost repetitive but eye-catching information from others, which can be harmful to conservation when the information is not evidence based (Anderson, 2014;Hart et al, 2020). In this case, we showed that media attention is transitory, as many trade events only received coverage years after their occurrence, after other eye-catching events had attracted the media's attention.…”
Section: Characteristics Of Media Reporting Around the Jaguar Tradementioning
confidence: 99%
“…Therefore, it is important to expand research on media discourses beyond the English-language media, and include media not only from the species' range states but also the other countries in the trade chain. Besides, due to its illicit nature, the investigation of IWT issues is challenged by uncertainties, and the media, as a powerful communication tool, may risk spreading misinformation (Hart et al, 2020). Thus, conservation researchers need to have a clear understanding of how the media portrays IWT issues in different countries and languages, and its influence on public attitudes and policies.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of news content on social media found that exposure to even one fake news post increases perceptions of the truthfulness of subsequent misleading posts (Pennycook et al, 2018). This is concerning given the growing concerns around the negative impacts of misinformation in conservation (Bergman et al, 2022; Ford et al, 2021; Hart et al, 2020). If there are repeated false claims on social media about the most pressing threats to a species, this may severely impact conservation efforts.…”
Section: Introductionmentioning
confidence: 99%